TRADE-OFF ANTARA MANAJEMEN LABA AKRUAL DAN RIIL PADA BANK KONVENSIONAL PUBLIK DI INDONESIA - Ontorael, Rianty; Geraldina, Ira (Jurnal Akuntansi dan Keuangan Indonesia, 2017)
Earnings management arises from a conflicting goal between agents and principals which basically means as managers’ intentions to manipulate accounting figures in the financial statement to achieve their own interests. There are two techniques of earnings management that are usually used by management: accrual earnings management and real earnings management. The objective of this study is to examine the effect of cost of earnings management on accrual and real earnings management and the trade-off relationship between accrual and real earnings management. Using 14 publicly listed banks in the Indonesia Stock Exchange during period 2009-2013, this study shows that costs of accrual and real earnings management have significant effects on accrual and real earnings management. However, this study did not find the evidence that there is a trade-off relationship betweeen accrual earnings management and real earnings management. The findings have implications regarding the use of costs of earnings management in considering type of earnings management’s decision in publicly listed banks in Indonesia.